Women in Mass Media in Under the Silver Lake (2018): A Saussure’s Semiotics Study - Amanda, Naura Fitri; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (MOZAIK HUMANIORA, 2024)
This study examines the portrayal of women in the mass media in a movie Under the Silver Lake (2018). This study used a qualitative method and Saussure’s semiotic theory to analyze women in the mass media in the movie, particularly on the connection between the portrayal of women and its meaning based on social conception. There are two types of mass media in the movie that are analyzed: print ads and magazines. The first focuses on the 1969 Tipalet print ads, and the second is from the 1970 Playboy magazine. The findings indicate that women in mass media are not merely portrayed as models or figures to promote a product. Instead mass media is inclined to use their portrayal as a medium to promote the ideas of women objectification. The portrayal of women in those mass media; thus, they often appear objectified, exploited, and undervalued. They are depicted in their most sexual appearance, which does not account for them as equal human beings. Such portrayals of women in conventional mass media provide the most harmful and unequal representation of women.